Validation of a tri-axial accelerometer for measuring physical activity in patients with subacute stroke - Kimura, Yosuke; Suzuki, Yoshiki; Kubo, Hiroki; Yoshida, Keishi; Ota, Tomohiro; Shimizu, Natsuki; Kanai, Masashi (Frontiers in Rehabilitation Sciences, 2025)
PurposeThis study aimed to validate the accuracy of the Active Style Pro HJA-750C (ASP) in measuring metabolic equivalents (METs) during walking and reaching tasks in individuals with subacute stroke using a respiratory gas analyzer as a reference.MethodsTwenty-three hospitalized patients with subacute stroke participated in this study. They performed sitting and standing reaching tasks, as well as walking while wearing a VO2 Master respiratory gas analyzer and ASP devices on both the paretic and non-paretic sides. The METs values recorded by the ASP were compared with those obtained using a VO2 Master respiratory gas analyzer. Pearson's correlation coefficients were calculated for each task, and Bland–Altman plots were used to assess the agreement between the two methods.ResultsThe ASP demonstrated good concurrent validity, with correlation coefficients of 0.71 and 0.74 for the sitting reaching task, 0.75 and 0.79 for the standing reaching task, and 0.83 and 0.85 for walking when the ASP was placed on the paretic and non-paretic sides, respectively. Bland–Altman analysis indicated no significant fixed or proportional errors. The ASP accurately measures METs whether worn on the affected or unaffected side of the waist.ConclusionThe ASP provides valid measurements of physical activity during walking and reaching tasks in patients with subacute stroke. These findings suggest that ASP is a valuable tool for monitoring physical activity in clinical rehabilitation settings.